Correction to: Value of PET imaging for radiation therapy (Strahlentherapie und Onkologie, (2021), 197, 9, (1-23), 10.1007/s00066-021-01812-2) - Lapa, Constantin; Nestle, Ursula; Albert, Nathalie L.; Baues, Christian; Beer, Ambros; Buck, Andreas; Budach, Volker; Buetof, Rebecca; Combs, Stephanie E.; Derlin, Thorsten; Eiber, Matthias; Fendler, Wolfgang P.; et al. (Strahlentherapie und Onkologie, 2022)
The original version of this article unfortunately contained a mistake. The copyright holder for this article was incorrectly given as “© Springer-Verlag GmbH Germany, part of Springer Nature 2021,” but should have been “© The Author(s) 2021.” The original article has been corrected.
CRIS-Team Scopus Importer:2023-03-08